A qualitative study of the impact of plexiform neurofibromas on need fulfilment in adults with neurofibromatosis type 1. (February 2019) - Heaney, Alice; Wilburn, Jeanette; Langmead, Shannon; Blakeley, Jaishri; Huson, Susan; Jim, Carly; McKenna, Stephen P
Objective: To explore the impact of plexiform neurofibromas on the lives of adults with neurofibromatosis type 1. Background: Neurofibromatosis type 1 is a complex neurogenetic syndrome that affects many aspects of health and functioning. A common manifestation of neurofibromatosis type 1 is plexiform neurofibromas, non-cancerous tumours that can cause disfigurement, pain and neurologic disability. Patient-reported outcome measures used in this condition have addressed symptoms and functional ability but not how the condition affects patients' lives, particularly, their ability to meet their human needs. Methods: Unstructured qualitative interviews were conducted with adults with neurofibromatosis type 1–associated plexiform neurofibromas in the United Kingdom and United States. Interviewees were encouraged to describe how plexiform neurofibromas affected their ability to meet their needs. Interviews were audio-recorded and transcribed verbatim. The UK and US transcripts were combined and theoretical thematic analysis was conducted. Results: In all, 42 interviews (United Kingdom = 20, United States = 22) were conducted. Transcripts revealed 696 statements on the impact of plexiform neurofibromas on need fulfilment. Five major themes emerged: appearance, relationships, independence, role fulfilment and pleasure. Conclusion: Neurofibromatosis type 1–associated plexiform neurofibromas have a major effect on individuals' ability to meet their needs. An understanding of need fulfilment will complement information generated from traditional patient-reported outcome measures, particularly in a multi-faceted syndrome such as neurofibromatosis type 1.